Metode Project Based Learning dalam Pembelajaran Bahasa Arab Perspektif Psikolinguistik - Novita Maula Salsabila; Setiyawan, Agung (Universitas Islam Negeri Alauddin, 2024)
Often in the learning process, teachers and students face various obstacles that hinder the effective achievement of learning objectives. Determining the appropriate method is a key factor in achieving learning objectives. One of the learning approaches currently attracting attention is Project-Based Learning (PjBL). This research aims to identify the effectiveness of Project-Based Learning (PjBL) in the Arabic language learning process from a psycholinguistic perspective. This study is a literature review where data is obtained from books, articles, and related literature. After data processing, analysis proceeds through three stages: data reduction, data presentation, and drawing conclusions. PjBL method is project-oriented and considered effective in cognitive, affective, and psychomotor aspects. Psycholinguistics in Arabic language learning cannot be ignored. The application of PjBL from a psycholinguistic perspective shows effectiveness in language acquisition, especially in Arabic language.